Work and social theory - Warren, Tracey (Sage, 2015)
This chapter identifies some of the most important theoretical debates within the sociology of work and employment. It provides an historical context by introducing the key theoretical approaches that marked the birth of sociology. The chapter shows the importance of this theoretical canon for developments in a discipline that span over two hundred years. Yet it also highlights absences from the canon, and identifies some of the most important theoretical ideas for the contemporary sociological understanding of work and employment that have emerged since. The chapter starts and ends by pointing readers to the contested meaning of the very concept of work. It concludes by reflecting on the purpose of social theorising.